Basal debris of the NEEM ice core, Greenland: a window into sub-ice-sheet geology, basal ice processes and ice-sheet oscillations - Blard, Pierre-Henri; Protin, Marie; Tison, Jean-Louis; Fripiat, Francois; Dahl-Jensen, Dorthe; Steffensen, Jørgen Peder; Mahaney, William C; Bierman, Paul R; Christ, Andrew J; Corbett, Lee B; Debaille, Vinciane; Rigaudier, Thomas; et al. (Journal of Glaciology, 2023)
We present new data from the debris-rich basal ice layers of the NEEM ice core (NW Greenland). Using mineralogical observations, SEM imagery, geochemical data from silicates (meteoric 10 Be, εNd, 87 Sr/ 86 Sr) and organic material (C/N, δ 13 C), we characterize the source material, succession of previous glaciations and deglaciations and the paleoecological conditions during ice-free episodes. Meteoric 10 Be data and grain features indicate that the ice sheet interacted with paleosols and eroded fresh bedrock, leading to mixing in these debris-rich ice layers. Our analysis also identifies four successive stages in NW Greenland: (1) initial preglacial conditions, (2) glacial advance 1, (3) glacial retreat and interglacial conditions and (4) glacial advance 2 (current ice-sheet development). C/N and δ 13 C data suggest that deglacial environments favored the development of tundra and taiga ecosystems. These two successive glacial fluctuations observed at NEEM are consistent with those identified from the Camp Century core basal sediments over the last 3 Ma. Further inland, GRIP and GISP2 summit sites have remained glaciated more continuously than the western margin, with less intense ice-substratum interactions than those observed at NEEM.